Pengembangan Bahan Ajar Matakuliah Biologi Sel Pada Program Studi Pendidikan Biologi di Universitas Nusantara PGRI Kediri - SAFITRI, DINI; ZUBAIDAH, SITI; GOFUR, ABDUL (Bioedukasi: Jurnal Pendidikan Biologi, 2014)
This research and development aims to produce teaching materials such as textbooks which are viable and validated by experts materials, media, and language, as well as validated by the student of biology education. The model used in this research and development is the 4D model proposed by Thiagarajan which consists of phases define, design, develop, and disseminate, but the stage of development carried out to develop stage. The trials were carried out, among others, by three expert lecturers and 31 students of fourth semester of biology education program. Expert lecturers consists matter experts, media specialists, and linguists. The test is done in two stages, the individual tests and test a small group of trial results and revised measures showed that the textbooks have categorized and ready for use in real learning. The resultÂ  of the test is some recommendations for developing the books, include language, matter, picture, illustration, and layout.